Minimizing Microbial Hazards for Fresh Fruits and Vegetables, Health and Hygiene - Gast, Karen L. B.; Holt, Kim (My University, 2000)
This publication describes food saftey and how to keep food and yourself safe.
MF2481_2000_12
Keywords: MF2481; Health and Safety; fruits and vegetables; MF